2007
DOI: 10.1063/1.2472273
|View full text |Cite
|
Sign up to set email alerts
|

Perfectly tetragonal, tensile-strained Ge on Ge1−ySny buffered Si(100)

Abstract: High-quality, tensile-strained Ge layers with variable thickness (>30nm) have been deposited at low temperature (350–380°C) on Si(100) via fully relaxed Ge1−ySny buffers. The precise strain state of the epilayers is controlled by varying the Sn content of the buffer, yielding tunable tensile strains up to 0.25% for y=0.025. Combined Raman analysis and high resolution x-ray diffraction using multiple off-axis reflections reveal unequivocally that the symmetry of tensile Ge is perfectly tetragonal, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 13 publications
2
76
0
1
Order By: Relevance
“…Tensilely strained Ge can be grown on InGaAs templates, as shown in a recent report of strain-enhanced photoluminescence at cryogenic temperatures (15); however, this approach is not compatible with Si-based CMOS technology. Similarly, SiGeSn has been proposed as a suitable growth template for the same purpose (10,16), but its epitaxy is quite challenging and still under development. Tensile strain can also be introduced in plastically relaxed Ge films grown on Si by using an annealing process to take advantage of the difference in thermal-expansion coefficients between Si and Ge (11).…”
mentioning
confidence: 99%
“…Tensilely strained Ge can be grown on InGaAs templates, as shown in a recent report of strain-enhanced photoluminescence at cryogenic temperatures (15); however, this approach is not compatible with Si-based CMOS technology. Similarly, SiGeSn has been proposed as a suitable growth template for the same purpose (10,16), but its epitaxy is quite challenging and still under development. Tensile strain can also be introduced in plastically relaxed Ge films grown on Si by using an annealing process to take advantage of the difference in thermal-expansion coefficients between Si and Ge (11).…”
mentioning
confidence: 99%
“…The Sn content in the poly-Si 1ÀxÀy Ge x Sn y layer is overestimated to be 3.1-4.0% from these Raman spectra results compared to the designed Sn content of 2%. Fang et al reported that the peak shift to the lower wavenumber of the Ge-Ge peak in the Raman spectra is also caused by the tensile strain in a Ge layer [17]. The reason of the overestimation of the Sn content in this study can be accounted for by the tensile strain in the poly-Si 1ÀxÀy Ge x Sn y layer owing to the difference of thermal expansion coefficients between SiO 2 and Si 1ÀxÀy Ge x Sn y .…”
Section: Resultsmentioning
confidence: 61%
“…The in-plane biaxial strain in the Ge epilayer was estimated from the shift in phonon vibration mode (∆ω) relative to bulk Ge, using the relation ∆ω = bε || , where b is a material parameter dependent on the material's phononic and elastic constants. Using the reported literature value of b = 415 cm 1 for Ge, 19 a tensile strain of ε || = 0.10% was deduced in the Ge-on-Si epilayer for the observed Raman shift. Moreover, for single-crystal Ge, only one active phonon mode contributes to Raman scattering in the (001) back scattering measurement orientation.…”
Section: A Materials Characterizationmentioning
confidence: 95%